2019
DOI: 10.1302/0301-620x.101b1.bjj-2018-0702.r1
|View full text |Cite
|
Sign up to set email alerts
|

The outcome and survival of metal-on-metal hip resurfacing in patients aged less than 50 years

Abstract: Aims The aim of this study was to report the implant survival and patient-reported outcome measures (PROMs) in a consecutive series of patients aged less than 50 years at the time of arthroplasty using the Birmingham Hip Resurfacing system (BHR), with a minimum follow-up of ten years. Patients and Methods A total of 226 patients with osteoarthritis of the hip, who underwent BHR and presented to a single surgeon, were included in the study. Survival of the implant was confirmed by cross-checking with the Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…Scholes et al 39 reported implant survival of 96.8% (95% CI 94.2 to 99.4) at 15 years in a cohort of 226 patients who underwent a BHR aged less than 50 years. Furthermore, patients experienced and maintained significant improvements in health and hip function scores, and activity scales beyond ten years postoperatively, and were equal to, or exceeded, age- and sex-matched normative data in more than 80% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholes et al 39 reported implant survival of 96.8% (95% CI 94.2 to 99.4) at 15 years in a cohort of 226 patients who underwent a BHR aged less than 50 years. Furthermore, patients experienced and maintained significant improvements in health and hip function scores, and activity scales beyond ten years postoperatively, and were equal to, or exceeded, age- and sex-matched normative data in more than 80% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients experienced and maintained significant improvements in health and hip function scores, and activity scales beyond ten years postoperatively, and were equal to, or exceeded, age- and sex-matched normative data in more than 80% of patients. 39…”
Section: Discussionmentioning
confidence: 99%
“…These modalities include femoral head core decompression, osteotomy, electrical stimulation, and bone grafting with muscle-pedicle bone grafts, vascular-pedicle bone grafts, and free vascularized bone grafts [10,[19][20][21]. If hip joint reconstruction is deemed necessary, hip resurfacing (HR) and THA remain the primary treatment modalities [56][57][58][59][60][61]. HR has had poor results historically [56,61], but more recent studies using meticulous patient selection in young adults have demonstrated satisfactory short-to medium-term outcomes.…”
Section: Current Controversies and Future Considerationsmentioning
confidence: 99%
“…Another reason to delay THA is its failure rate -5-15% [28][29][30][31] -with 7-28% of patients left with post-operative CHP [32][33][34]. As THA implants have a life expectancy ranging from 10 to 25 years [30,[35][36][37] many surgeons consider that under 50 years of age it is wiser to delay this surgical procedure as much as possible [38][39][40][41]. When THAs are not advisable, hip joint denervation is an option that has been performed for over one hundred years.…”
Section: Introductionmentioning
confidence: 99%